2022
DOI: 10.1101/2022.09.21.508923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bub1 kinase acts as a signalling hub for the entire Cryptococcus neoformans spindle assembly checkpoint pathway

Abstract: Cryptococcus neoformans (Cn) is an important human pathogen and a model system for basidiomycetes. Here we carry out a dissection of its spindle assembly checkpoint (SAC), focusing on Bub1 and Bub3. In many eukaryotes, including humans, Saccharomyces cerevisiae and Schizosaccharomyces pombe, Bub1 underwent gene duplication, generating paralogues referred to as Bub1 and BubR1 (or Mad3). Bub1 has upstream signalling functions at kinetochores, whilst BubR1/Mad3 is a component of the downstream mitotic checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Here we have demonstrated that the checkpoint signalling roles of Mps1 kinase, Mad1 and Mad2 and their molecular interactions are very well conserved in Cryptococcus neoformans. In a second study, we demonstrated that Bub1 and Bub3 functions are also very well conserved [46]. One important difference in the SAC is that Cryptococcus lacks a BubR1/Mad3 gene as, unlike in humans, S.cerevisiae and S.pombe, the CnBub1 gene hasn't undergone duplication and CnBub1 carries out the functions of both Bub1 (as a kinetochore-bound SAC signalling scaffold) and Mad3 (as part of the diffusible APC/C inhibitor) [46].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Here we have demonstrated that the checkpoint signalling roles of Mps1 kinase, Mad1 and Mad2 and their molecular interactions are very well conserved in Cryptococcus neoformans. In a second study, we demonstrated that Bub1 and Bub3 functions are also very well conserved [46]. One important difference in the SAC is that Cryptococcus lacks a BubR1/Mad3 gene as, unlike in humans, S.cerevisiae and S.pombe, the CnBub1 gene hasn't undergone duplication and CnBub1 carries out the functions of both Bub1 (as a kinetochore-bound SAC signalling scaffold) and Mad3 (as part of the diffusible APC/C inhibitor) [46].…”
Section: Discussionmentioning
confidence: 76%
“…In a second study, we demonstrated that Bub1 and Bub3 functions are also very well conserved [46]. One important difference in the SAC is that Cryptococcus lacks a BubR1/Mad3 gene as, unlike in humans, S.cerevisiae and S.pombe, the CnBub1 gene hasn't undergone duplication and CnBub1 carries out the functions of both Bub1 (as a kinetochore-bound SAC signalling scaffold) and Mad3 (as part of the diffusible APC/C inhibitor) [46]. Here we have also shown that Mps1 phospho-regulation of Mad1 is conserved in Cryptococcus.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…To study if the Bub1 kinase activity required for shugoshin's function is evolutionarily conserved in C. neoformans, we utilized the kinase-dead (bub1-kd) mutant of Bub1. In vitro assays reported earlier (Leontiou et al, 2022) revealed that Bub1 could phosphorylate the reconstituted human H2A containing nucleosomes, and kinase-dead mutants of Bub1 fail to phosphorylate. We performed a genetic interaction assay by scoring the TBZ sensitivity of sgo1Δ, bub1-kd, and sgo1Δ bub1-kd mutants (Fig 5B).…”
Section: The Kinase Activity Of Bub1 Is Dispensable For the Function ...mentioning
confidence: 85%